Effects of compression socks on pain and peripheral responses during and following marathon running - Babault, N.; Deley, G.; Gardon-Mollard, C.; Benigni, J. P.; Allaert, F. A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Compression garments are now commonly used by athletes during training and competitions to delay fatigue, reduce pain during efforts (Chatard et al., 2004) and also to optimise recovery (Kraemer et al., 2001). They may favour peripheral circulation, blood flow return and therefore decrease metabolic toxin stasis. If many athletes regularly reported these effects, few data are available concerning their effects during marathon runs. Therefore this study aimed to assess the effects of wearing class II elastic socks (18-21 mmHg) on subjective ratings and peripheral circulation when applied during marathon runs. Methods: This study was conducted during the "Marathon de Paris". Eighty-six comparable subjects (i.e., males/females proportion, marathon performance, body mass index, internal gastrocnemius vein diameter) were considered in this study (n = 43 in each group). Their mean age ± SD were 43 ± 8 years old and none reported any venous insufficiency. Compression socks (18-21mmHg) were proposed to marathoner who accepted to wear them during the race (Compression Sock Group CSG) and compared to a control group who did not wear them (Control Group CG). Marathoners had a Doppler examination before and after the race and described their feeling at the end of the race and during the 4 following days using a visual analogic scale (from 0 to 100). Results: At the end of the race and compared to CG, the CSG group described lower muscular pain 33 ± 25 vs. 49 ± 28 (p<0.01), lower muscular leg tiredness 44 ± 21 vs. 57 ± 25 (p<0.01) and lower leg swelling 9 ± 18 vs. 18 ± 22 (p<0.01). The diameter of the internal gastrocnemius vein was also lower 5.1 ± 1.4 mm vs. 5.7 ± 1.5 mm (p<0.05). While pain decrease was comparable during the 4 following days, recovery of muscular leg tiredness was significantly improved in the CSG group (p<0.01). Discussion: These results clearly demonstrate the positive effects of wearing elastic compression socks during long duration efforts. The pain reduction during the marathon may reduce the risk of a premature stop and may contribute to the last supplementary effort at the end of the race. The additional positive effects on the recovery kinetic is also important for the runners` comfort and especially in elite athletes which may have to practice frequently with short recovery delays. In conclusion, wearing compression socks may contribute to increase muscular adaptation and recovery.